Management of pesticide residues in select spices - Aaruni P S (Department of Agricultural Entomology, College of Agriculture, 2016)
The present study entitled “Management of pesticide residues in select spices” was carried out at Department of Agricultural Entomology, College of Agriculture, Vellayani during 2014-16. The main objective of the work was to standardize household techniques to decontaminate pesticide residues in select spices. Investigation was conducted to evaluate the efficacy of different decontamination techniques in removing pesticide residues of organophosphate and synthetic pyrethroid from six select spices viz., peppermint leaves, coriander leaves, red chilli (dry), cumin, fennel and ginger. Among the different decontamination methods adopted in peppermint, dipping leaves in KAU Veggie wash 10 ml L-1, 2 per cent synthetic vinegar and 2 per cent turmeric for five minutes were significantly superior in the removal of organophosphate and synthetic pyrethroid insecticides, to the tune of 34.8 to 57.30, 27.74 to 58.42 and 29.19 to 54.80 per cent respectively. In the case of coriander leaves, the same treatments were found to be effective in removing up to 81.11 per cent, 76.56 per cent and 72.81 per cent residues respectively. Washing with these solutions and then cooking for 10 minutes also indicated a similar trend in the insecticide removal. Open pan and close pan cooking of both peppermint and coriander leaves did not show significant variation in the removal of both organophosphate and synthetic pyrethroid insecticides. Comparatively lesser percentage removal was observed in the case of synthetic pyrethroids than organophosphates when subjected to different treatments. In dry chilli, the reduction in the residues due to sauting in frying pan for two minutes was 22.74 to 72.59 per cent. Cooking chilli powder in water for 20 minutes removed 39.33 to 85.54 per cent residues. Removal of fruit stalk, drying and powdering removed 17.73 to 74.20 per cent whereas removal of chilli seeds, drying and powdering resulted in only 2.62 to 16.00 per cent reduction in residues. Soaking dry chilli in KAU Veggie wash (10 ml L-1) for five minutes was found to be effective in removing 14.51 to 89.50 per cent of the residues. Dipping cumin and fennel in 2 per cent synthetic vinegar or 2 per cent turmeric for five minutes effectively removed insecticides up to 60 per cent. Cumin seeds and water when tested separately after boiling showed that pesticide concentration was more in cumin seeds (27.50 to 84.60 per cent) compared to that in water (9.05 to 74.30 per cent). Dipping ginger in 2 per cent tamarind (prepared from commercial tamarind paste) or 2 per cent common salt for five minutes removed insecticides up to 45.08 per cent and 53.60 per cent respectively. Peeling of ginger, cooking or processing (dry ginger) was effective in removing 48.15 to 65.99, 52.83 to 77.11 and 57.31 to 77.20 per cent of the residues respectively. Organoleptic test conducted showed that washing with different decontamination solutions does not affect the taste and over all acceptability of the select spices evaluated except cumin and fennel dipped in 2 per cent turmeric. It is concluded that, household techniques to decontaminate pesticide residues in select spices showed that dipping of spices viz., red chilli, coriander leaves, peppermint leaves in KAU Veggie wash (10 ml L-1) for five minutes effectively removed residues of organophosphate and synthetic pyrethroid insecticides to the extent of 14.51 to 89.50, 25.40 to 81.11 and 34.8 to 57.30 per cent respectively. However, KAU Veggie wash was not effective in decontaminating cumin seed, fennel and ginger. In case of peppermint leaves, dipping in two per cent synthetic vinegar and two per cent turmeric for five minutes followed by three washings were found to be effective in the removal of 27.74 to 58.42 per cent of organophosphates and 29.34 to 49.20 per cent of synthetic pyrethroids. Dipping coriander leaves in two per cent synthetic vinegar and two per cent turmeric for five minutes followed by three washings were found to be effective in removing 45.98 to 81.11 per cent of organophosphates and 14.80 to 50.95 per cent of synthetic pyrethroids. Dipping in 2 per cent synthetic vinegar or 2 per cent turmeric solution was the most effective treatments in decontaminating cumin and fennel whereas in ginger, dipping in 2 per cent tamarind or 2 per cent common salt removed 35.03 to 64.30 per cent and 25.45 to 53.60 per cent residues respectively.